Reference Book for Pancasila Learning Based on 21st Century Skills and Tri Kaya Parisudha Values - Nirmayani, L. Heny; Yudiana, I Kadek Edi (Jurnal Pendidikan Multikultural Indonesia, 2023)
Character education and learning outcomes for elementary school students are still relatively low. One factor that ensures student success is the role of the teacher. Therefore, the relevant effort to be carried out is to provide an understanding to students as prospective elementary school teachers in designing and implementing learning innovations to form a generation that is intelligent and has character by the demands of 21st-century learning and implementing the Tri Kaya Parisudha concept. This research aims to develop a 21st-century-based Pancasila learning reference book containing Tri Kaya Parisudha for Elementary School Teacher Education Study Program students. This research is design and product development research (Design and Development) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects in this research were two experts, ten students, and eight elementary school teachers. The data analysis method used is the descriptive analysis method. The research results show that 21st-century learning containing the Tri Kaya Parisudha in the Pancasila learning reference book has very good validity for students in the Elementary School Teacher Education Study Program. It is proven by the results of data analysis of the validity test of language and content experts that obtain a very good category. Likewise, the responses of students and teachers in elementary schools show an average score (mean) in the very good category.